Analisis Kemampuan Berpikir Kritis Siswa Kelas 5 SD dalam Soal Cerita Penjumlahan dan Pengurangan. - Nurcholis Nurcholis; Feri Faila Sufa (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The objectives of the study are (1) to determine the critical thinking skills of 5th grade students of SD Negeri 03 Jumapolo, Karanganyar. (2) to determine the factors underlying the critical thinking skills of 5th grade students of SD Negeri 03 Jumapolo, Karanganyar. This study used qualitative research that lasted for 2 weeks. Data collection techniques in this study used observation, interviews, and documentation. The results of this study indicate that (1) the critical thinking skills of 5th grade students of SD Negeri 03 Jumapolo, Karanganyar in solving story problems on addition and subtraction material do not fully have critical thinking skills because there is one aspect that has not been fulfilled, namely not being able to conclude addition and subtraction material through story problems. (2) The factors that influence critical thinking skills in 5th grade students of SD Negeri 03 Jumapolo, Karanganyar are 2 factors, namely psychological factors and physiological factors.